Taxonomy of genus Campylaspis G. O. Sars, 1865 (Cumacea, Nannastacidae) from Sergipe Sub-Basin and Campos Basin - DUDA, Maria Luiza de França (2023)
Campylaspis constitutes the most diverse genus within the Nannastacidae family. From the 205 species described worldwide 29 occur in the South Atlantic, and 14 of them are recorded from Brazilian waters. However, the diversity is still underestimated due to the lack of specialists in the group. The main objective of this study is to conduct an investigation of the taxonomy and bathymetric distribution of the Campylaspis in the Sergipe Sub-Basin and the Campos Basin, Brazil to reveal its diversity and identify ecological preferences. Specimens were collected through the Descartes (Sergipe) and PMAR-BC (Rio de Janeiro) surveys. The abiotic data includes geographic coordinates, depth, and sediment type. The collection of specimens was carried out using a box corer, and after collection, they were classified at the family level and preserved in 75% ethanol. Then, specimens from the Nannastacidae family were identified at the lower level following the specific literature. By the end of the study, a total of 239 Campylaspis specimens collected at 7 stations in the Sergipe and 126 stations in Campos Basins were analyzed. The faunistic composition checklist presents a total of 19 species, with distribution along the continental slope ranging between 984 and 1060 meters in the Sergipe Sub-Basin, and between 79 and 847 meters in the Campos Basin. Among these, three are under description as new to science (Campylaspis n. sp.15, Campylaspis n. sp.16, and Campylaspis n. sp.17) and 14 morphotypes are potentially new species. Additionally, two other morfotypes were identified as Campylaspis cf. nitens and Campylaspis cf. nuda, already known for Recife (Brazil), but recorded for the first time in the Sergipe Sub-Basin. Based on the results of the bathymetric study, 5 species (Campylaspis sp.6, Campylaspis sp.8, Campylaspis sp.9, Campylaspis sp.11 and Campylaspis sp.13) are distributed at depths of less than 200 meters, 3 species (Campylaspis sp.3, Campylaspis sp.5 and Campylaspis sp.12) at depths up to 400 meters, 7 species at depths between 650 and 800 meters (Campylaspis sp.1, Campylaspis sp.2, Campylaspis sp.4, Campylaspis sp.7, Campylaspis sp.14, Campylaspis sp.15 and Campylaspis sp.16), and 4 species (Campylaspis sp.10, Campylaspis sp.17, Campylaspis cf. nitens and Campylaspis cf. nuda) at depths beyond 950 meters. Therefore, the present study increased the number of Campylaspis species in the South Atlantic and expanded the knowledge of continental slope diversity including an updated key for the genus from the Atlantic Ocean.